Aerodynamic interference between high-speed slender bodies - Chaplin, Ross (Cranfield University, 2009)
Significant aerodynamic interference can occur between high-speed bodies in close proximity. A complex flowfield develops where shock and expansion waves from a generator body impinge upon the adjacent receiver body. The pressure and flow angularity changes which occur across these disturbances modify the body aerodynamics. The aim of this research is to quantify the aerodynamic interference effects for multi-body configurations and understand the relevant flow physics. The interference aerodynamics for slender bodies in a supersonic flow were investigated through a parametric wind tunnel study. The receiver bodies were finned and un-finned configurations. The effect of lateral and axial body separations, receiver incidence and the strength of the disturbance field were investigated. Measurements included forces and moments, surface pressures and flow visualisations. Supporting computations using steady-state, viscous predictions provided a deeper understanding of the underlying aerodynamics and flow mechanisms. Good agreement was found between the measured and predicted interference loads and surface pressures for all configurations. The interference loads are strongly dependent upon the axial impingement location of the primary shockwave. These induced loads change polarity as the impingement location moves aft over the receiver. The magnitude of the interference loads increase when the receiver is at incidence and are amplified by up to a factor of three when rear fins are attached. In general, the interference loads are larger for a stronger disturbance flowfield. The centre of pressure location is substantially affected and the static stability of the finned receiver changes in some configurations. The effect of the aerodynamic interference on the body trajectories was assessed using an unsteady, Euler prediction in combination with a 6DOF dynamic model. This shows aerodynamic ii interference can cause a collision between the bodies. Moreover, the initial interference loads dominate the subsequent body trajectories and static modelling can be used to evaluate the dynamic trajectories.